2015
DOI: 10.1177/0963662515595348
|View full text |Cite
|
Sign up to set email alerts
|

Polarizing news? Representations of threat and efficacy in leading US newspapers’ coverage of climate change

Abstract: This study examines non-editorial news coverage in leading U.S. newspapers as a source of newspapers. Also, across all newspapers, climate impacts and actions to address climate change were more likely to be discussed separately than together in the same article. Implications for public engagement and ideological polarization are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 46 publications
4
93
0
3
Order By: Relevance
“…In particular, it is important for future research to consider how action‐oriented information about climate change can be presented in such a way as to increase hope but not reduce fear. Combining impacts and actions information, rather than focusing on actions exclusively, may be one approach . In fact, the actions plus impacts text condition did not have any significant negative indirect effects via fear, only positive effects through hope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it is important for future research to consider how action‐oriented information about climate change can be presented in such a way as to increase hope but not reduce fear. Combining impacts and actions information, rather than focusing on actions exclusively, may be one approach . In fact, the actions plus impacts text condition did not have any significant negative indirect effects via fear, only positive effects through hope.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, hope, which prior research has shown is positively related to climate policy support and activism, is often thought to be in short supply among Americans when it comes to climate change . News stories about climate change tend to emphasize dramatic, threatening consequences, while sending a muddled message about possible actions that can mitigate its effects . Given that media are the public's primary sources of information about climate change, such coverage may engender a feeling of hopelessness and, in turn, undermine engagement with the issue .…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, Painter and Gavin (2016) 2011 climate skepticism was still in evidence across a range of U.K. national newspapers. A close relationship has been found to exist between the leanings of national newspapers in the United Kingdom and the United States and their coverage of climate change; with right-leaning papers being much more likely to include climate skeptic editorials and commentaries and written by climate change denialists (Carvalho, 2007;Feldman et al, 2015;Painter & Gavin, 2016). However, there is considerable variation across countries in the amount of space given to climate change skeptics (see Painter, 2011).…”
Section: Journalistic Values and Normsmentioning
confidence: 99%
“…In conclusion, our study demonstrates that messages linking GM to global food security generally seem to increase favorable attitudes toward GM crops, irrespective of whether the weather-related problems mention climate change. Returning to our real-world example from the study's introduction, these findings would suggest that Bill Gates' statement in the Wall Street Journal linking GM to food security in Africa in the context of climate change might indeed have led to increased support for GM's use, even among the more conservative readership of the Wall Street Journal (Feldman, Hart, & Milosevic, 2015). However, among certain sub-groups, particularly liberals, our results suggest that the same statement from Bill Gates might appeal less, given that our findings show that the explicit mention of "climate change" in our message resulted in less favorable attitudes among liberals than the implicit mention.…”
Section: Discussionmentioning
confidence: 89%